Impact of Type 2 Diabetes Mellitus on the Epidemiological-Clinical and Paraclinical Characteristics of Acute Heart Failure Seen at the Soavinandriana Hospital Center, Antananarivo Madagascar - Raharinavalona SA; Miandrisoa RM; Randrianomanana TV; Andrianasolo RL; Rakotomalala ADP (Research Reports in Clinical Cardiology, 2024)
Sitraka Angelo Raharinavalona,1 Rija Mikhaël Miandrisoa,1 Tsikinirina Valisoa Randrianomanana,2 Radonirina Lazasoa Andrianasolo,2 Andrianirina Dave Patrick Rakotomalala2 1Cardiovascular Diseases and Internal Medicine Departments, Soavinandriana Hospital Center, Antananarivo, Madagascar; 2Endocrinology Department, Joseph Raseta Befelatanana University Hospital Center, Antananarivo, MadagascarCorrespondence: Sitraka Angelo Raharinavalona, Cardiovascular Diseases and Internal Medicine Departments, Soavinandriana Hospital Center, Rue Dr MOSS, Soavinandriana, BP: 6 Bis, Antananarivo, Madagascar, Email sitrakarah@gmail.comBackground: The association diabetes mellitus - acute heart failure (AHF) is frequent and a source of significant morbidity and mortality.Objective: The present study aimed to determine the impact of type 2 diabetes (T2DM) on the epidemiological-clinical and paraclinical characteristics of acute heart failure (AHF).Methods: This was a retrospective cross-sectional study, carried out over a period of 2 years. The diagnosis of diabetes mellitus was made according to the criteria of the American Diabetes Association. The diagnosis of AHF is established by the signs and symptoms of heart failure; increased levels of brain natriuretic peptide (BNP); and systolic and/or diastolic dysfunction on echocardiography.Results: 63 T2DM and 120 non-T2DM consecutive patients were selected. Age (≥ 50 years in men and ≥ 60 years in women) (OR=2.08 [1.31– 5.14]), dyslipidemia (OR=3.95 [1.82– 8.75]), microalbuminuria (OR=6.06 [1.69– 27.3]) and overweight/obesity (OR=3.32 [1.33– 13.5]) were more frequent in T2DM. The clinical profile of T2DM was marked by the rise in mean systolic arterial pressure (p=0.0368), arterial oxygen desaturation (p=0.0214), New York Heart Association (NYHA) IV breathlessness (OR=2.06 [1.04– 4.08]); and paraclinical by left ventricular hypertrophy (OR=2.67 [1.24– 5.77]), segmental kinetic disorder (OR=1.96 [1.04– 3.67]) and ischemic heart disease (OR=1.98 [1.09– 3.92]). Diabetics received more statin (OR=2.06 [1.05– 4.03]) and less spironolactone (OR=0.29 [0.13– 0.64]).Conclusion: T2DM is associated with poor profile of AHF. Adequate management of cardiovascular risk factors, including diabetes, could thus minimize the occurrence of AHF and improve this profile.Keywords: acute heart failure, cardiovascular risk factors, coronary artery disease, Madagascar, type 2 diabetes mellitus